Perendaman Benih Mucuna (Mucuna bracteata) Pada Suhu Air Yang Berbeda Dalam Percepatan Perkecambahan Benih - Lince Romauli Panataria; Sri Pratywi; Efbertias Sitorus; Meylin Kristina Saragih (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2025)
Generative propagation of Mucuna bracteata is complicated and requires special treatment to germinate. Mucuna has a thick, rigid, and impermeable seed coat, which becomes a mechanical barrier to water or gas entry, making the imbibition process challenging to occur. Breaking dormancy in mucuna seeds aims to increase germination. This study aims to determine the effect of soaking time for mucuna seeds (Mucuna bracteata) at different water temperatures on breaking dormancy. This study used a completely randomized design factorial. This study consists of 2 treatment factors. The first factor is the length of soaking (L), which consists of 3 levels: 30 minutes, 60 minutes and 90 minutes. The second factor is water temperature (K), which consists of 3 levels: 30 °C, 60 °C and 90 °C. Data analysis used variance analysis and simple regression analysis. The results of the study showed that water temperature had a significant effect on increasing germination power, accelerating germination, increasing the number of normal sprouts, and the dry weight of mucuna (Mucuna bracteata) sprouts..